Characterization of the Spatial and Temporal Distribution of Nipah Virus Spillover Events in Bangladesh, 2007–2013. (17th January 2018) - Cortes, Maria C; Cauchemez, Simon; Lefrancq, Noemie; Luby, Stephen P; Jahangir Hossain, M; Sazzad, Hossain M S; Rahman, Mahmudur; Daszak, Peter; Salje, Henrik; Gurley, Emily S
Abstract: Nipah virus is a zoonotic virus harbored by bats and lethal to humans. Bat-to-human spillovers occur every winter in Bangladesh. However, there is significant heterogeneity in the number of spillovers detected by district and year that remains unexplained. We analyzed data from all 57 spillovers during 2007–2013 and found that temperature differences explained 36% of the year-to-year variation in the total number of spillovers each winter and that distance to surveillance hospitals explained 45% of spatial heterogeneity. Interventions to prevent human infections may be most important during colder winters. Further work is needed to understand how dynamics of bat infections explains spillover risk. Abstract : We explore the drivers of the spatiotemporal distribution of the highly lethal Nipah virus and demonstrate that year-to-year variability in the number of spillovers is linked to annual temperature differences and that spatial variability is associated with the distance to surveillance hospitals.